PROJEÇÃO DE DISTÂNCIAS COMO MÉTODO AUXILIAR NA CLASSIFICAÇÃO DE ARROZ IRRIGADO QUANTO A ADAPTABILIDADE E ESTABILIDADE - SILVA, Gabi Nunes; SILVA JUNIOR, Antônio Carlos da; SANT'ANNA, Isabela de Castro; CRUZ, Cosme Damião; NASCIMENTO, Moysés; SOARES, Plínio César (Brazilian Journal of Biometrics, 2019)
Rice (Oryza sativa) represents one of the most important grains in terms of economic value, standing out as the second most cultivated cereal and one of the most consumed in the world. The objective of this work was to propose the Distances Projection method to aid in the classification of irrigated rice genotypes for adaptability and stability. The design was randomized blocks in three locations and evaluated in four years, making a total of 12 environments. Previously, variance analysis and adaptability and stability analyzes were performed using the Eberhart and Russel and Centroid methodologies for subsequent graphic analysis using the Distance Projection Method proposed in this study. The projections were constructed under two principles, that is, complement of the determination coefficient or distance of Gower. The results indicated great potential of the proposed graphic method. The graphical representations provided by the Distance Projection method facilitated the recognition of the interaction pattern G x E of the evaluated rice genotypes, considering the difficulties of interpretation and disagreement between the results of the Eberhart and Russell and Centroid methodologies.